KEHARMONISAN HUBUNGAN ANTARA ETNIS BALI DENGAN ETNIS LAMPUNG (Studi di Kabupaten Lampung Selatan) - Afero, Deni; Hartoyo, Hartoyo (SOCIOLOGIE, 2013)
This study aims to determine the relationship between ethnic Balinese with non-ethnic Balinese, why ethnic conflict ethnic Lampung Bali with rapidly enlarging, how the governments role in conflict resolution, and how the reality of the condition of harmony in South Lampung regency. This study uses qualitative methods. Collecting data using in-depth interview techniques. Determination informen purposive sampling to select some members of the public who are directly involved in the conflict in South Lampung Lampung and some traditional leaders. The information is analyzed in order to draw conclusions in accordance with the reality on the ground conditions with the method of data reduction, data presentation, drawing conclusions and verification. The results showed that. First, the tendency to act improperly Balinese ethnic make another ethnic unrest led to unite to fight the action. Secondly, there is the waking ego and attitude tit conducted between ethnic Ethnic Bali and Lampung. Third, the government has not been able to resolve the ethnic conflict in South Lampung. Fourth, the relationship between ethnic harmony, especially among ethnic ethnic Balinese with non-Bali is low.Keywords: Harmony, relationships, ethnic